Implications of the Use of Electronic Certificates in Proving Land Rights According to the Civil Procedure Law - Noor, Aslan; Wassir, Bekawita; Anggraini, Ira; Rahmaniah, Erlin (SAINTIS Publishing, 2024)
The development of digital technology has encouraged reforms in land administration in Indonesia, one of which is the application of electronic certificates as evidence of land rights. The use of electronic certificates aims to increase efficiency, transparency, and legal certainty in the process of proving in court. This study aims to analyse the legal validity and practical aspects of the use of electronic certificates in the process of proving land rights according to civil procedural law. The study is based on several key regulations, including the Basic Agrarian Law (UUPA), Government Regulation (PP) No. 24 of 1997, PP No. 18 of 2021, Minister of Agrarian and Spatial Planning/National Land Agency Regulation (Permen ATR/BPN) No. 1 of 2021, and the Electronic Information and Transaction Law (UU ITE). The results show that electronic certificates are legally recognised as valid evidence in court. These certificates have the same evidentiary power as physical certificates and can be used as a strong evidentiary tool in land rights disputes. In addition, the electronic land registration process enables more effective recording and management of land data, reduces the potential for certificate forgery, and increases the efficiency and security of the evidentiary process in court. However, in practice, the use of electronic certificates still faces several challenges, such as limited digital infrastructure, protection of personal data, and resistance from people who are used to physical certificates. Another obstacle is the doubt of some parties regarding the evidentiary power of electronic certificates in court. Therefore, socialisation efforts, strengthening regulations, and increasing technological and infrastructure capacity are needed to support the optimal implementation of electronic certificates.